From the Past to the Future: Integrating Archaeology and Conflict Resolution in Northern Ireland. (February 2015) - Horning, Audrey; Breen, Colin; Brannon, Nick
<x content-type="archive" xml:space="preserve">Abstract</x> Contested understandings about the past continue to reify the divided character of post-Troubles Northern Ireland. In particular, the unresolved legacies of the extension of English control over Ireland in the late sixteenth and early seventeenth centuries through warfare and plantation continue to structure daily lives in the province. Yet the archaeological record of this period complicates the accepted dichotomous narratives through highlighting complexity. These nuances, however, have been lost in recent decades as an overly simplistic model of colonizer versus colonized has emerged as the dominant political paradigm. The management and presentation of sites associated with the process of plantation can arguably create the space necessary to bridge the divide, and to challenge accepted understandings. Cross-community engagement in the process of archaeological discovery and interpretation on plantation-period sites in Northern Ireland highlights the critical role archaeology can play in peace and reconciliation in post-conflict societies.